Impact of COVID-19 on Children and Young Adults With Type 2 Diabetes: A Narrative Review With Emphasis on the Potential of Intermittent Fasting as a Preventive Strategy - Elmajnoun, Hala K.; Faris, MoezAlIslam E.; Uday, Suma; Gorman, Shaun; Greening, James E.; Haris, Parvez I.; Abu-Median, Abu-Bakr (Frontiers in Nutrition, 2021)
Background: The world is still struggling to control the COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The level of uncertainty regarding the virus is still significantly high. The virus behaves differently in children and young adults. Most children and adolescents are either asymptomatic or have mild symptoms. They generally have a very good prognosis. However, it is not well-known whether children and young adults with type 2 diabetes are at risk of getting a severe infection of COVID-19. Many Muslim children with type 2 diabetes have been performing dawn to dusk fasting during the month of Ramadan, before and during the COVID-19 pandemic, and the impact of this on their health has not been well investigated. Previous studies in adults have suggested that intermittent fasting may be beneficial in different ways including reversal of type 2 diabetes and prevention of COVID-19 infection. Objective: The primary aim of this narrative review is to summarise the impacts of the COVID-19 pandemic on children and young adults with type 2 diabetes, and to identify the knowledge gaps in the literature. It also explores the potential of intermittent fasting in reversing the pathogenesis of diabetes and highlighting how this approach could prevent these patients from developing chronic complications. Methods: This narrative review has been produced by examining several databases, including Google Scholar, Research Gate, PubMed, Cochrane Library, MEDLINE (EBSCO), and Web of Science. The most common search terms used were “COVID-19 AND Children”, “SARS-CoV-2 AND/OR Children”, “COVID-19 AND Diabetes” “COVID-19 Epidemiology”, “COVID-19 AND Ramadan fasting”, “COVID-19 and Intermittent fasting.” All the resources used are either peer-reviewed articles/reports and/or official websites of various media, governmental and educational organisations. Results: Having reviewed the currently limited evidence, it has been found that the incidence of COVID-19 among children with type 2 diabetes seems to be not much different from children without diabetes. However, these patients are still vulnerable to any infection. Several studies have reported that prevention programmes such as intermittent fasting are effective to protect these groups of patients from developing any complications. Moreover, observing Ramadan fasting as a type of intermittent fasting could be beneficial for some children with established diabetes, prediabetes and people at risk. Conclusion: Children and young adults with type 2 diabetes are not at risk of severe COVID-19 infection as the case in adults with diabetes. More research is needed to identify the impact of COVID-19 and to investigate the efficacy and safety of intermittent fasting, including Ramadan fasting, among these age groups. Implementing these cost-effective programmes may have a great impact in minimising the incidence of diabetes. Moreover, this could be effective particularly at prediabetes stage by preventing these people from going onto develop type 2 diabetes and taking medications for the rest of their life and protecting people from complications linked to disease and infection.